A novel strategy to design a multilayer functionalized Cu2S thin film counter electrode with enhanced catalytic activity and stability for quantum dot sensitized solar cells. Issue 2 (22nd January 2020) - Wu, Libin; Lin, Zhengmeng; Feng, Pengyu; Luo, Liping; Zhai, Lanlan; Kong, Fantai; Yang, Yun; Zhang, Lijie; Huang, Shaoming; Zou, Chao
Abstract : Multilayer Cu2 S/ITO/CuZnMo films are designed as CEs for QDSCs, having the merits of enhanced conductivity and stability, and high catalytic activity. Abstract : As the essential component of a quantum dot-sensitized solar cell (QDSC), the counter electrode (CE) plays an important role in electron transfer and catalytic reduction acquisition throughout the device. A novel route to design multilayer functionalized Cu2 S thin films as CEs with high catalytic activity and enhanced stability, as well as large specific surface area and high conductivity, is presented. Firstly, Mo-based films were prepared by magnetron sputtering on a glass substrate, and then porous CuZnMo conductive films were formed by etching with hydrochloric acid. Secondly, indium tin oxide (ITO) film was sputtered onto the porous structure to act as a protective layer, and a porous ITO/CuZnMo structured film was obtained after optimization. In the third step, multilayer Cu( x )/ITO/CuZnMo structured films were acquired by sputtering Cu films. Finally, multilayer Cu2 S( t )/ITO/CuZnMo functionalized film CEs were obtained via in situ sulfidation of sputtered Cu films. The functions of conduction and resistance to electrolyte corrosion were produced and enhanced by annealing an ITO layer at high temperature prior to Cu deposition, while catalytic activity enabled by Cu2 S was realized from Cu film sulfidation. The multilayer Cu2 S/ITO(500 °C)/CuZnMo functionalized films exhibit high catalytic activity and enhanced stability for resistance to electrolyte corrosion. Taking multilayer Cu2 S/ITO(500 °C)/CuZnMo films as CEs, the QDSCs demonstrated good stability of power conversion efficiency (PCE) after 500 h of irradiation, from an initial 4.21% to a final 4.00%. Furthermore, the thickness of Cu2 S film modulated by the duration of Cu sputtering was investigated. It was found that the QDSCs using multilayer Cu2 S(40 min)/ITO/CuZnMo functionalized film with a Cu2 S thickness of 1.2 μm as CE exhibit the best performance, and the R ct value was 0.57 Ω. The best photovoltaic performance with a PCE of 5.21% ( V oc = 533.1 mV, J sc = 18.80 mA cm −2, FF = 52.84%) was achieved under AM 1.5 radiation with an incident power of 100 mW cm −2 . This design of a multilayer functionalized CE introduces potential alternatives to the common brass-based CE for long-term QDSCs with high performance.